Prevalence and Predictors of Antibiotic Prescriptions at Primary Healthcare Facilities in the Dodoma Region, Central Tanzania: A Retrospective, Cross-Sectional Study - Richard James Mabilika; Gabriel Shirima; Emmanuel Mpolya (MDPI AG, 2022)
Background: Accelerated by the misuse or overuse of antibiotics, antibiotic resistance remains a global public health threat. We report the prevalence and predictors of antibiotic prescriptions in primary healthcare facilities in Dodoma, Tanzania. Methods: This retrospective cross-sectional study by medical records review was conducted in the Dodoma region, Central Tanzania. Results: In this study, children < 5 years accounted for over 45% (474/1021) of the patients consulted. The majority, 76.3% (779/1021), of consultations had an antibiotic prescribed; amoxicillin and cotrimoxazole were the most prescribed. Over 98% (766/779) of the antibiotics prescribed were on the National Essential Medicines List, but only 45% (429/779) of the antibiotic prescriptions adhered to the Standard Treatment Guidelines. The prescribing of antibiotics by clinical officers was almost 2.55 times higher than that among medical doctors (Odds Ratio (OR) = 2.546; 95% Confidence Interval (CI): 1.359, 4.769; p = 0.0035). Patients with pneumonia and upper respiratory tract infection were 15.9 (OR = 15.928; 95% CI: 2.151, 17.973; p = 0.0067) and 2 (OR = 2.064; 95% CI: 1.184, 3.600; p = 0.0106) times more likely to be prescribed antibiotics, respectively. Conclusions: We, therefore, report high rates of antibiotic prescriptions, poor adherence to standard treatment guidelines and high levels of antibiotic prescribing practices among prescribers with a diploma in clinical medicine.